THE RIITESH SINHA OSCILLATOR (RSO): A NOVEL MARKET MOMENTUM INDICATOR BASED ON PIVOT PRICE EXPONENTIAL MOVING AVERAGE (EMA) - Sinha, Riitesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper introduces the Riitesh Sinha Oscillator (RSO), a novel momentum indicator derived from the Pivot Exponential Moving Average (PEMA). Unlike traditional oscillators, RSO measures market momentum by analyzing the relative difference between short-term and long-term PEMA values. The formula for RSO is defined as: where PEMA is calculated as the Exponential Moving Average (EMA) of the pivot point of a share price: The RSO offers traders and analysts an efficient method to gauge market momentum, identify trend reversals, and optimize entry and exit points. This paper presents the mathematical formulation, methodology, and practical applications of RSO in financial markets.